Bioreproductive Variation in Populations of the Freshwater Mussel Anodonta cygnea (Linnaeus, 1771) Depending on the Aquatic Environment in which They Grow - Mariana Cristina Arcade; Mioara Costache; Daniela Radu; Marinela Gancea; Carmen Anca Anghelescu; Carmen Georgeta Nicolae (Scientific Papers Animal Science and Biotechnologies)
The freshwater clams Anodonta Cygnea are part of the aquatic population of the 3 studied fishponds. The witness pond (Wp) is similar in characteristics to their natural rearing environment, pond 1 (P2) is populated with uniform fish stock in terms of age, weight and species variation, and pond 3 (P3) is similar to pond 1 in terms of populations and characters mentioned above, but the difference is that here a platform of 8 floating cages has been introduced here, where polyculture rearing of two-summer-old fish is carried out. The variations in the growth of the clams are visibly influenced by the specific characteristics of the studied ponds, thus in the control pond the bivalves had a weaker growth rate, in the second pond they had visibly higher values compared to the control group, in terms of total weight and standard lengths recorded. In pond number 3 (P3), characters such as total weight, standard lengths, shell mass and internal contents were compared with the two variants studied, so that the best results were obtained in pond 3 where integrated multitrophic aquaculture is applied.